2019
DOI: 10.3389/fneur.2019.00825
|View full text |Cite
|
Sign up to set email alerts
|

Default Mode Network Connectivity Predicts Emotion Recognition and Social Integration After Traumatic Brain Injury

Abstract: Moderate-severe traumatic brain injury (TBI) may result in difficulty with emotion recognition, which has negative implications for social functioning. As aspects of social cognition have been linked to resting-state functional connectivity (RSFC) in the default mode network (DMN), we sought to determine whether DMN connectivity strength predicts emotion recognition and level of social integration in TBI. To this end, we examined emotion recognition ability of 21 individuals with TBI and 27 healthy controls in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 81 publications
1
13
0
Order By: Relevance
“…Thus, the disconnection between bilateral SFG and these regions may be linked with the functional deficits in cognitive integration in the acute mTBI patients. Some recent resting-state fMRI BOLD connectivity studies has identified disconnection functional coupling between the prefrontal cortex and these regions [40,41], which are consistent with our results. In addition, the CBF disconnection between the right CPL and bilateral ITG as well as the right FG was also been identified in mTBI patients, suggesting a disruption of the cerebellar-subcortical-cortical loop, which is partly consistent with the previous restingstate functional connectivity studies that indicate the CPL-FG disconnection and the abnormality of the cerebellum network in mTBI [42][43][44].…”
Section: Neural Plasticitysupporting
confidence: 93%
“…Thus, the disconnection between bilateral SFG and these regions may be linked with the functional deficits in cognitive integration in the acute mTBI patients. Some recent resting-state fMRI BOLD connectivity studies has identified disconnection functional coupling between the prefrontal cortex and these regions [40,41], which are consistent with our results. In addition, the CBF disconnection between the right CPL and bilateral ITG as well as the right FG was also been identified in mTBI patients, suggesting a disruption of the cerebellar-subcortical-cortical loop, which is partly consistent with the previous restingstate functional connectivity studies that indicate the CPL-FG disconnection and the abnormality of the cerebellum network in mTBI [42][43][44].…”
Section: Neural Plasticitysupporting
confidence: 93%
“… 44–48 Additionally, altered connectivity has been demonstrated in the default mode network and other brain regions following TBI. 49–52 However, the quality of the BOLD signal depends on an intact neurovascular structure, and TBI is known to result in alterations of brain vasculature. 53–57 As such, fMRI studies in TBI should be interpreted with caution.…”
Section: Diagnostic Biomarkersmentioning
confidence: 99%
“…Those brain regions with synchronously fluctuating activities form intrinsic connectivity networks (ICNs) (95) ICNs are often characterized by independent component analysis (ICA) of resting-state lowfrequency (typically ranging from ∼0.01 to 0.1 Hz) fMRI data. Among different ICNs, the abnormalities of default mode network (DMN) have been frequently associated with TBI (96)(97)(98)(99), and a very recent systematic review revealed that the most frequently studied MRI-based brain connectivity biomarkers for mild TBI to date are global functional connectivity and DMN functional connectivity (along with DTI measures of FA) (100).…”
Section: Functional Magnetic Resonance Imaging Approachesmentioning
confidence: 99%
“…Following partial recovery of consciousness after an acute TBI that resulted in coma, patients in a minimally conscious or confused state showed partially preserved intra-DMN connectivity while such connectivity was absent in those that remained comatose ( 97 ). The DMN connectivity returned to a normal level upon full recovery of consciousness ( 97 ), although persistently altered DMN connectivity (>1 year since injury) predicted poor emotion recognition and social integration ( 96 ) as well as cognitive dysfunction ( 104 ) in TBI patients. While promising, more longitudinal studies with larger sample size are warranted prior to the wide adoption of fMRI for clinical use in TBI.…”
Section: Current Status Of Omics Data In Moderate/severe Tbimentioning
confidence: 99%